2011
DOI: 10.1002/pip.1129
|View full text |Cite
|
Sign up to set email alerts
|

19%‐efficient and 43 µm‐thick crystalline Si solar cell from layer transfer using porous silicon

Abstract: We present a both‐sides‐contacted thin‐film crystalline silicon (c‐Si) solar cell with a confirmed AM1.5 efficiency of 19.1% using the porous silicon layer transfer process. The aperture area of the cell is 3.98 cm2. This is the highest efficiency ever reported for transferred Si cells. The efficiency improvement over the prior state of the art (16.9%) is achieved by implementing recent developments for Si wafer cells such as surface passivation with aluminum oxide and laser ablation for contacting. The cell h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
151
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 247 publications
(152 citation statements)
references
References 16 publications
0
151
0
1
Order By: Relevance
“…We further exploited the advantages of the all-back-contact design in our nanostructured solar cell by optimizing the pitch between the two contacts. For thick Si solar cells with the all-back-contact design, the pitch is normally 4400 mm, which allows less complicated fabrication processes such as screen-printing of metal contacts [38][39][40] . Previous studies have found that the fill factor (FF) was the only parameter that depended on the pitch in thick Si solar cells 41,42 .…”
mentioning
confidence: 99%
“…We further exploited the advantages of the all-back-contact design in our nanostructured solar cell by optimizing the pitch between the two contacts. For thick Si solar cells with the all-back-contact design, the pitch is normally 4400 mm, which allows less complicated fabrication processes such as screen-printing of metal contacts [38][39][40] . Previous studies have found that the fill factor (FF) was the only parameter that depended on the pitch in thick Si solar cells 41,42 .…”
mentioning
confidence: 99%
“…Technologies that enable the fabrication of thin c-Si layers in the range of 1 μm [2] up to 40 μm [3,4] directly on glass have been proposed. However, c-Si thin-films of a few micrometers suffer from a significantly reduced optical absorption in the red and nearinfrared regions of the solar spectrum.…”
mentioning
confidence: 99%
“…В последнее время пористый кремний активно ис-пользуется в электронике и оптоэлектронике в каче-стве ориентирующих подложек для роста различных наноструктур [1,2], как широкозонный материал для комплементарных металлооксидных полупроводниковых технологий (CMOS-технологий) [3], для фотодетекто-ров [4] и солнечных элементов [5], для одномерных фотонных кристаллов [6,7], химических и биологических сенсоров [8] и т. д. Такие приборы находят применение в различных отраслях промышленности, в том числе в военной, космической технике и атомной энергетике, где они могут подвергаться воздействию ионизирующего излучения. Дефекты, возникающие в CМОS-структурах на кремнии под воздействием жесткого ионизирующего облучения, приводят к частичному или полному отказу аппаратуры вследствие окисления кремния после обра-зования дефектов и потери его свойств [9].…”
Section: Introductionunclassified